Validation of the long‐term assessment of hypothalamic‐pituitary‐adrenal activity in rats using hair corticosterone as a biomarker. Issue 3 (14th November 2014) - Scorrano, Fabrizio; Carrasco, Javier; Pastor‐Ciurana, Jordi; Belda, Xavier; Rami‐Bastante, Alicia; Bacci, Maria Laura; Armario, Antonio
Abstract : The evaluation of chronic activity of the hypothalamic–pituitary–adrenal (HPA) axis is critical for determining the impact of chronic stressful situations. However, current methods have important limitations. The potential use of hair glucocorticoids as a noninvasive retrospective biomarker of long‐term HPA activity is gaining acceptance in humans and wild animals. However there is no study examining hair corticosterone (HC) in laboratory animals. The present study validates a method for measuring HC in rats and demonstrates that it properly reflects chronic HPA activity. The HC concentration was similar in male and female rats, despite higher total plasma corticosterone levels in females, tentatively suggesting that it reflects free rather than total plasma corticosterone. Exposure of male rats to 2 different chronic stress protocols (chronic immobilization and chronic unpredictable stress) resulted in similarly higher HC levels compared to controls (1.8‐fold). HC also increased after a mild chronic stressor (30 min daily restraint). Chronic administration of 2 different doses of a long‐acting ACTH preparation dramatically increased HC (3.1‐ and 21.5‐fold, respectively), demonstrating that a ceiling effect in HC accumulation is unlikely under other more natural conditions. Finally, adrenalectomy significantly reduced HC. In conclusion, HC measurement in rats appears appropriate to evaluate integrated chronic changes in circulating corticosterone.—Scorrano, F., Carrasco, J., Pastor‐Ciurana, J., Belda, X., Rami‐Bastante, A., Bacci, M. L., Armario, A., Validation of the long‐term assessment of hypothalamic–pituitary–adrenal activity in rats using hair corticosterone as a biomarker. FASEB J. 29, 859–867 (2015). www.fasebj.org